Characterization of a common carp intelectin gene with bacterial binding and agglutination activity. Issue 108 (January 2021) - Li, Jinyi; Chen, Yanru; Gu, Wei; Xu, Fojiao; Li, Hua; Shan, Shijuan; Sun, Xiaojie; Yin, Miao; Yang, Guiwen; Chen, Lei
Abstract: Intelectin (ITLN) is a type of glycan-binding lectin involved in many physiological processes and some human diseases. Here we report a common carp intelectin (cITLN). Like other orthologs, cITLN also contains a conserved fibrinogen-related domain (FReD) and a unique intelectin domain, expresses in all the tissues tested with the highest level in the hindgut, and responds to bacterial challenge in the acute phase. We also expressed cITLN in Escherichia coli ( E. coli ) system, and the purified recombinant cITLN could neither affect the surface of bacteria nor inhibit the growth of bacteria, but it can agglutinate both gram-positive and gram-negative bacteria in a calcium-dependent manner. The cITLN's ability of agglutination of gram-positive bacteria is stronger than that of gram-negative bacteria. This is probably because recombinant cITLN could binding peptidoglycan (PGN) with a higher degree to lipopolysaccharide (LPS). Our results of cITLN provided new insight into the function of intelectin in the intestinal mucosal immunity. Highlights: One homologue of intelectin named cITLN with a FReD and a unique intelectin domain was characterized in common carp. The cITLN is expressed in all tissues we tested and upregulated after challenge of A. hydrophila . The cITLN can bind to both LPS and PGN. Maybe it's the early step for cITLN to exert its bacterial binding and agglutinating.